Sweden : 2013 Article IV Consultation. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This 2013 Article IV Consultation highlights Sweden's economic growth and policies. Sweden's economy appears to be slowing together with its main Nordic and European trading partners. The IMF report discusses that there is a scope to improve the fiscal framework, by ensuring it remains sufficiently countercyclical. Given the importance of Swedish banks for the region, improving financial stability in Sweden would also contribute to financial stability across the Nordics, as would additional progress toward cross-border burden-sharing agreements. Structural reforms are also expected to add to resilience and growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet